2022
DOI: 10.1155/2022/4625368
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans and Candida dubliniensis in Periodontitis in Adolescents and Young Adults

Abstract: Aim. This study aims to evaluate the association of Candida albicans and Candida dubliniensis with periodontitis in adolescents and young adults in a Moroccan population. Methods. 426 subjects aged between 12 and 25 years were recruited for the study. A pool of plaque sample was taken. Samples were cultured on Sabouraud Chloramphenicol medium at 37°C for 24–48 hours and then identified by the Vitek 2 YST system. Clinical data and presence of Candida albicans and Candida dubliniensis were analyzed using Jamovi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…C. dubliniensis is related to oral candidiasis, especially in immunocompromised individuals, such as HIV-infected individuals 37 . Furthermore, this yeast has already been isolated from periodontal pockets of adolescents 38 . In the biofilm, many metabolites are produced, which may be associated with worsening cases of periodontitis caries 39 .…”
Section: Discussionmentioning
confidence: 99%
“…C. dubliniensis is related to oral candidiasis, especially in immunocompromised individuals, such as HIV-infected individuals 37 . Furthermore, this yeast has already been isolated from periodontal pockets of adolescents 38 . In the biofilm, many metabolites are produced, which may be associated with worsening cases of periodontitis caries 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common oral infections have been reported to be caused by C. albicans , a pathogenic fungus [ 76 ]. Moreover, numerous studies have indicated the presence of C. albicans in subjects with periodontitis [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. dubliniensis is an infrequent and cryptic pathogen; thus, its clinical features remain to be elucidated. Most C. dubliniensis isolates have been isolated from the respiratory tract [ 10 ], especially oral samples [ 17 , 18 ]; however, recent reports have suggested that rare fungi can cause invasive infections as well [ 11 , 12 ]. Although rare, one case of C. dubliniensis fungemia during the treatment of COVID-19 has been described in the literature [ 19 ].…”
Section: Discussionmentioning
confidence: 99%